The Effect of Corporate Social Responsibility Disclosure on Firm Value with Environmental Performance as a Moderating Variable - I Putu Bayu Suda; I Made Karya Utama (Review of Ethics in Sustainable Finance and Accounting, 2025)
As industrial rivalry intensifies, companies face mounting pressure to boost their performance and market valuation. Nevertheless, prioritizing profits above all else tends to result in the disregard of social and environmental responsibilities which a tendency particularly pronounced in manufacturing, where operations involving waste disposal directly affect ecological systems. Consequently, firms must not only implement but also publicly disclose their Corporate Social Responsibility (CSR) commitments, thereby demonstrating accountability to stakeholders while simultaneously cultivating investor confidence and enhancing corporate value. This study examines the relationship between Corporate Social Responsibility (CSR) disclosure and firm value, with environmental performance as a moderator, focusing on manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2020-2022. Using a sample of 58 companies (174 firm-year observations), CSR disclosure was measured using the Global Reporting Initiative (GRI) G4 index, firm value using Tobin’s Q, and environmental performance using PROPER ratings from the Ministry of Environment. Moderated regression analysis reveals that CSR disclosure has a significant positive effect on firm value (β = 8.426, p < 0.05). Furthermore, environmental performance significantly strengthens this relationship (interaction β = 2.791, p < 0.05), indicating that the CSR-firm value linkage is amplified for companies with superior environmental ratings. The model explains 7.9% of firm value variation. These findings support stakeholder, legitimacy, and signaling theories, demonstrating that environmental performance enhances investor confidence in CSR activities. The study provides implications for corporate sustainability strategy, investor decision-making, and environmental policy design in emerging markets.